The Effect of Government ICT Policy and Technology Leadership on Teacher’s Technology Integration - Setia, Shinta; Aufar, Sulthan Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to analyze the influence of principals' technology leadership on teachers' technology integration and the moderating role of government ICT policy in all public junior high schools in Surabaya in the new normal era. The research sample consisted of 100 respondents, including 25 principals and 75 teachers from State Junior High Schools in Surabaya with high technology implementation. The data in this study were successfully collected through questionnaires. All collected data will be processed using the PLS-SEM method in the SmartPLS 3.0 software by setting a significance level of 5%. The results indicate that technology leadership positively and significantly affects teachers' technology integration. Further, the results show the role of government ICT policy, which has been proven to strengthen the positive influence of technology leadership on teachers’ technology integration.